Designing and Explaining a Policy-Making Model for Increasing the Credibility of Sharia Resolutions in Islamic Banking in Afghanistan - Najeeh, Sayed Hujjatullah; Rabiee Mandejin, Mohammad Reza; Araei, Vahid; Momeni, Mandan (Management Strategies and Engineering Sciences, 2027)
The present study was conducted with the aim of designing and explaining a policy-making model for increasing the credibility of Sharia resolutions in Islamic banking in Afghanistan. Given the re-establishment of Islamic governance and the necessity of fully aligning banking operations with Sharia, the absence of a clear and codified framework for the Sharia policy-making process is considered the most important challenge facing the country’s banking system. In this study, the credibility of Sharia resolutions is understood as a concept beyond mere jurisprudential correctness and includes jurisprudential robustness, legal coherence, transparency, acceptability, and effective enforcement. This study was conducted using a qualitative approach and thematic analysis. Data were collected through semi-structured interviews with 15 experts in the fields of Islamic banking, jurisprudence, law, and economics, who were selected through purposive sampling based on expert criteria. The sample size was determined according to the principle of theoretical saturation. Data analysis was carried out in three stages of open, axial, and selective coding using MAXQDA software. Open coding led to the identification of 532 initial codes, which were categorized during axial coding into three axial codes: “Sharia governance and supervision,” “laws, regulations, and institutional frameworks,” and “institutional and governance factors.” The central phenomenon of the study was named “institutional-social legitimation of Sharia resolutions.” Adopting a process-oriented and systemic perspective, the present study, for the first time, presents an indigenous model adapted to the political, administrative, and cultural structure of Afghanistan, which seeks to increase the credibility of Sharia resolutions through redefining the roles and functions of Sharia institutions, improving approval and supervision processes, and strengthening interactions among key actors. The credibility of Sharia resolutions is not merely a jurisprudential issue, but rather a macro-level managerial and policy-making issue that requires the design of multidimensional and coordinated policies at various institutional, legal, educational, and supervisory levels.